Paper 3: Impact of the Indoor Climate on the Performance of Building Materials Contaminated with Salt Mixtures. (February 2014) - De Clercq, Hilde; Godts, Sebastiaan; Hayen, Roald
<x content-type="archive" xml:space="preserve">Abstract</x> Archaeological sites are essentially submitted to decay phenomena inherent on their history as well as the environment to which they are exposed after excavation. The history of such archaeological sites is particularly related to their long-term underground conservation conditions during which they were subject to salt migration into the architectural remains. It is well known that soluble salts present in building materials can cause damage, mainly by producing stresses in the substrate. A lot of research has been done in the past concerning the behaviour of salts in built constructions. However, most studies include single salts, of which the deliquescence points are well documented, while in situ one mostly finds complex salt mixtures, which makes the conservation strategy much more intricate. The environmental conditions to minimize damage of salt-laden porous building materials can be modelled using a computer program ECOS capable of predicting the crystallization behaviour of salt mixtures. To use the model data of quantitative salt analyses are required as input. The program is then able to predict from a thermodynamic point of view which minerals will exist in the solid state under specified climatic conditions. This paper deals with the results of a systematic investigation of the salt contamination of the building materials of the Coudenberg site and a prediction of the behaviour of the salt mixture related to the actual climate, as part of the environmental assessment.